Clarifying the taxonomic status and distributions of the spider species collected during the Leonhard Schultze expeditions in western and central southern Africa (Arachnida: Araneae) - Haddad, Charles R.; Marusik, Yuri M. (Zootaxa, 2019)
Purcell (1908) and Simon (1910) described or reported 181 spiders from southern Africa based on the material collected by German zoologist and anthropologist Leonhard Schultze in 1903‒1905. The expedition route passed through several countries/territories that have since changed their boundaries and/or names. The two mentioned papers included 32 localities in three modern countries, aside from broader geographical regions (e.g. Hereroland) without specified localities. In this paper, we list all species reported or described, their current taxonomic status, provide the correct data about the countries from where these species were described, and their current distributions based on taxonomic publications. Purcell and Simon treated 81 and 100 species respectively, of which 49 and 67 respectively were new. A sizeable proportion of these species have since been transferred to other genera or proposed as synonyms. In evaluating all of the localities provided in the treatments of species in these two papers, as well as subsequent taxonomic literature, we found that 25 of the 68 nominative species treated by Purcell and 38 of the 92 species treated by Simon had incorrect distribution data in the World Spider Catalog (2019). We provide revised distribution information for all of these, and discuss the importance of correct information in the preparation of national faunistic lists.